Impact of financial capital, social capital, and business digitalization on business sustainability of SMEs in Indonesia - Pardiman Pardiman; Jeni Susyanti; Dwi Fita Heriyawati; Zuhkhriyan Zakaria; Masyhuri Masyhuri (Jurnal Manajemen dan Pemasaran Jasa, 2022)
SMEs have significant challenges amid a pandemic that is crippling the country's economy to survive and continue to struggle from bankruptcy. So, this paper analyzes the impact of financial capital, social capital, and business digitalization in improving business sustainability and finds out which variables are marketing strategies in mediating the direct influence between these three variables. Data collection using a questionnaire instrument using a survey technique. The research sample was 93 respondents as SME business owners. The research period was carried out from June to September 2021. After the data is collected, then tested using SEM-PLS using Warppls 5.0 software. The study found that financial capital can improve business sustainability, and social capital can also affect business sustainability; the same is valid for business digitization which can improve business sustainability for SME actors. Therefore, SME business actors need to pay attention to the business capital, then social capital to the community in the long term, and digitalization to improve businesses' ability to survive in a pandemic. Furthermore, we hope that this research will expand understanding to SMEs business owners to be more vigilant about several factors that can make a business go bankrupt, especially in a pandemic situation. However, the limitation of this study lies in the research sample, which only examines one province so that future researchers can compare it with other provinces. And in this study, it was found that the marketing strategy has not been successful in mediating, so it still needs to be discussed further.